Neuromodulation of Aerobic Exercise—A Review - Heijnen, Saskia; Hommel, Bernhard; Kibele, Armin; Colzato, Lorenza S. (Frontiers in Psychology, 2016)
Running, and aerobic exercise in general, is a physical activity that increasingly many people engage in but that also has become popular as a topic for scientific research. Here we review the available studies investigating whether and to which degree aerobic exercise modulates hormones, amino acids, and neurotransmitters levels. In general, it seems that factors such as genes, gender, training status, and hormonal status need to be taken into account to gain a better understanding of the neuromodular underpinnings of aerobic exercise. More research using longitudinal studies and considering individual differences is necessary to determine actual benefits. We suggest that, in order to succeed, aerobic exercise programs should include optimal periodization, prevent overtraining and be tailored to interindividual differences, including neuro-developmental and genetically-based factors.